The Role of Social Networks on building Awareness and social responsibility to achieve Environmental Sustainability in Bangladesh - A.B.M. Kamal Pasha; Maria Maha Jabin; Sagar Mozumder; Mahfuza Parveen (Sang Pencerah: Jurnal Ilmiah Universitas Muhammadiyah Buton, 2021)
With the benefit of globalization and access to data, unceremonious populations came to use social platforms largely used by several ages. Nonetheless, natural problems have been triggering universal effects, just as concerns of social feebleness. Natural mindfulness mixings new application propensities, performing another socially skilled stance. This analysis plans to separate the influence of relational organizations on natural mindfulness and the social responsibility of several ages. We employ the structure of the quantitative and distinctive study, by approaching the Primary Condition Establishing. The results feature that people who are presented with data (recordings, photographs, messages) acknowledged with social commitment and natural supportability are impacted in the progress of social and ecological mindfulness. However, all ages familiarized the most marginal approaches for responses in the quest for data on natural and social issues. This is appropriate to society, presentation organizations, government offices, and organizations to advance deeds and data on social and ecological obligation and connect all Ages in maintainable development.